The Exploitation of Heterosis for Yield and its Components of Tomato Hybrids for Use as Commercial Variety Development - Quamruzzaman, A. K. M.; Akter, L.; Islam, F. (European Journal of Applied Sciences, 2022)
A study was conducted in tomato to estimate the magnitude of heterosis for yield and yield related components at the Olericulture Division of Horticulture Research Centre, BARI during the winter season of 2021-22. Appreciable heterosis was found over better parents for all the traits studied in a desirable direction. Significant negative better parent heterosis was expressed for days to first flowering (4 combinations), days to 50% flowing (6 combinations), days to first harvest (7 combinations), and days to fruit maturity (8 combinations), while significant positive better parent heterosis was noticed in seven and three cross combinations for number of fruits per plant and single fruit weight, respectively. In our study, five cross combinations, viz., F1 203 (25.65%), F1 1501 (14.34%), F1 2101 (14.32%), F1 2301 (15.62%) and F1 2501 (16.22%) showed significantly positive better parent heterosis for higher yield. Six combinations were found to have significant positive heterosis with higher values in F1 1903 (21.95%), F1 2001 (19.62%), F1 2101 (12.84%) for TSS, while the significant negative better parent heterosis for TYLCV infection and leaf sucking pest infestation varied from -100% to 0.00%. Thus, it is evident from the data that, based on better parent heterosis of different yield and yield contributing traits, the cross combinations viz., F1 203, F1 1501, F1 2101, F1 2301 and F1 2501 may be investigated further for developing better hybrid tomato varieties.